Tolerância do alho (Allium sativun L.) cultivar BGH aos 492 herbicidas Prometryne e Oxadiazon - SEDIYAMA, MARIA APARECIDA NOGUEIRA; SILVA, JOSÉ FRANCISCO DA; CARDOSO, ANTONIO AMÉRICO; CASALI, VICENTE WAGNER DIAS (Revista Ceres, 2015)
.